Increasing Ebola transmission behaviors 6 months post-vaccination: Comparing vaccinated and unvaccinated populations near 2018 Mbandaka Ebola outbreak in the Democratic Republic of Congo. Issue 51 (17th December 2021) - Hoff, Nicole A.; Bratcher, Anna; Mukadi, Patrick; Ahuka, Steve; Kabamba, Michel; Musene, Kamy; Halbrook, Megan; Dzogong, Camille; Mwamba, Guillaume Ngoie; Mbala, Placide; Kelly, J. Daniel; Kompany, Jean Paul; et al.
Abstract: Background: In 2018, the Democratic Republic of the Congo (DRC) declared its 9th and 10th Zaire ebolavirus (EBOV) outbreaks, in the Equateur province (end: July 2018), and in the eastern provinces including North Kivu (end: June 2020). The DRC Ministry of Health deployed the rVSV-vectored glycoprotein (VSV-EBOV) vaccine in response during both outbreaks. Methods: A cohort of vaccinated and unvaccinated individuals from the Equateur province were enrolled and followed prospectively for 6 months. Among participants included in this analysis, 505 were vaccinated and 1, 418 were unvaccinated. Differences in transmission behaviors pre- and post- outbreak were identified, along with associations between behaviors and vaccination. Results: There was an overall increase in the proportion of both unvaccinated and vaccinated individuals in Mbandaka who participated in risky activities post-outbreak. Travel outside of the province pre-outbreak was associated with vaccination. Post-outbreak, vaccinated individuals were less likely to participate in funeral traditions than unvaccinated individuals. Conclusion: A net increase in activities considered high risk was observed in both groups despite significant efforts to inform the population of risky behaviors. The absence of a reduction in transmission behavior post-outbreak should be considered for improving future behavior change campaigns in order to prevent recurrent outbreaks.